Quantitative detection of SARS‐CoV‐2 RNA in nasopharyngeal samples from infected patients with mild disease. Issue 4 (5th January 2021) - Bustos, Patricia; Tambley, Carolina; Acevedo, Alejandra; Andrade, Winston; Leal, Gabriel; Vidal, Deyanira; Roldán, Francisco; Fasce, Rodrigo; Ramírez, Eugenio
Abstract: Diagnosis of severe acute respiratory syndrome coronavirus 2 (SARS‐COV‐2) cases is based on the count of real‐time reverse transcription‐plymerase chain reaction (RT‐PCR) positive people. Viral load by real‐time RT‐PCR has been suggested as a biomarker of the SARS‐CoV‐2 infection. However, the association of viral load and severity of the disease is not yet resolved. Nasopharyngeal samples from 458 patients were tested by RT‐PCR for SARS‐CoV‐2 diagnosis. Relative quantitation was made by the comparative threshold cycle (ΔΔ C t ) formula between ORF1ab viral and RNase P housekeeping genes. Absolute viral load was calculate using a reference positive control. Most prevalent clinical signs were cough (75.8%), myalgia (66.7%), and fever (48.5%). Hypertension (18.2%), neurological diseases (15.1%), and asthma and hypothyroidism (12.1%) were most frequent comorbidities. Fever, either as an exclusive symptom or combined with others, was associated with high viral loads ( 2 ‐ ∆ ∆ C t range, 35.65–155.16; 4.25–4.89 log10 RNA copies/test]). During the first week after onset of symptoms in mild patients up to 60 years‐old was detected the peak of viral load. Children under 10 years old have a high viral load (313.84; 2.50) in the first 2 days postinfection with a sharp decline thereafter. Cases between 10 and 49 years old mostly showed low and moderate viral load during the first 2 days postinfection (range, 0.03 to 17.24; −1.50 to 1.24). Patients over 60 years old have high viral load up to the second week after the onset of symptoms (range, 25.32–155.42; 1.40–2.19), indicating the longer presence of the virus in them. These findings suggest the viral load in nasopharyngeal swabs would help to monitor the SARS‐CoV‐2 infection in mild coronavirus disease 2019 cases. Highlights: Our research highlights the quantitative detection of SARS‐CoV‐2 in patients with mild COVID‐19 disease and the different viral load according to the age range of patients.